Effect of responsiveness and problem resolution on guest experience (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Taking into account the ever-evolving expectations about service, the objective of this study is to investigate the connection that exists between the quality of customer service and the level of satisfaction that is experienced by visitors who are staying at three-star hotels that are situated in metropolitan areas. As the hospitality industry continues to recover and adapt in the wake of the epidemic, there has been an increase in the amount of pressure placed on mid-tier hotels to provide service quality that is in accordance with both digital and personalised standards. Within the context of this particular market sector, the objective of this research is to study which factors of service quality—specifically, responsiveness, empathy, assurance, reliability, and tangibility—have the greatest impact on the amount of enjoyment that is experienced by visitors. The findings of this study have practical relevance for hotel managers who are interested in enhancing the quality of their interactions with customers and increasing their competitiveness in urban hospitality marketplaces. This study draws on the outcomes of prior research by making use of several models and empirical data that are now available.